Analysis The Determinants Affecting Banking Performance - Karnasi, Reniati; Elgi, Afrizal (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The research aims to test the effect of bank-specific and macroeconomic factors on bank performance in Indonesia. The research uses hypothetical testing to examine the determinants affecting bank performance. This study uses panel data regression to analyze the data. The samples are determined by purposive sampling method used 34 commercial banks listed on Bursa Efek Indonesia (BEI) with 238 unit-observed during the period 2017 to 2023. The results show bank size, bank capital, liquidity, and inflation rate have a positive effect on net interest margin. Furthermore, this study can be used as a reference for investors and banking management.